A stator voltage switching strategy for efficient low speed operation of DFIG using fractional rated converters. (September 2015) - Rudraraju, Venkata Rama Raju; Chilakapati, Nagamani; Saravana Ilango, G.
Abstract: This paper presents a scheme for extending low speed operation of a wind driven Doubly Fed Induction Generator (DFIG) with limited rating converters (30%). In this scheme, a low voltage is applied to the stator at rotor speeds below the normal range (0.7 p.u.) while the nominal voltage is applied when the rotor speed is above this range. The switch-over to a lower stator voltage below a threshold speed facilitates to maintain the operational efficiency with the same fractional rated converters. Simulations results of a typical 250 kW DFIG in Matlab/Simulink environment reveal that, a lower stator voltage increases the generator efficiency at lower speeds without exceeding (limited) rating of the rotor side power converter. Typically the speed range is extended by 20% when reduction in voltage is 42%. With a 250 kW generator the energy harvested over one year is increased by 61.1 MWh with the proposed scheme. The scheme is simple, economical and can be implemented through speed sensor and contactors. Experiments on a laboratory test set up demonstrate the efficacy of the proposition. Highlights: Presents a scheme for extending low speed operation of a DFIG. With limited rating converters (30%). Low voltage is applied to stator at rotor speeds below the normal range (0.7 p.u.). Nominal voltage is applied to stator when the rotor speed is above 0.7 p.u.